2017
DOI: 10.1002/ajmg.a.38527
|View full text |Cite
|
Sign up to set email alerts
|

Wieacker–Wolff syndrome with associated cleft palate in a female case

Abstract: Wieacker-Wolff syndrome is a rare congenital syndrome with few reported cases in the current literature. It is traditionally described in males as an X-linked recessive disorder associated with congenital contractures of the feet, progressive neurologic muscular atrophy, and intellectual delay caused by ZC4H2 mutations. The purpose of this paper is to present a female individual with a classic phenotype and cleft palate, a previously undescribed finding in this syndrome. Recent reports have demonstrated that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 8 publications
1
16
0
Order By: Relevance
“…Detailed clinical descriptions are presented in Supporting Information Results. In the clinical evaluation, we also included publicly accessible information of three females reported to DECIPHER and all families and simplex cases published to date (Godfrey et al, ; Hirata et al, ; Kondo et al, ; May et al, ; Okubo et al, ; Zanzottera et al, ). A compilation of the main ( ≥ 30%) clinical features of affected males and females from these 42 families is given in Table and of the additional less common clinical features (< 30%) in Table S2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Detailed clinical descriptions are presented in Supporting Information Results. In the clinical evaluation, we also included publicly accessible information of three females reported to DECIPHER and all families and simplex cases published to date (Godfrey et al, ; Hirata et al, ; Kondo et al, ; May et al, ; Okubo et al, ; Zanzottera et al, ). A compilation of the main ( ≥ 30%) clinical features of affected males and females from these 42 families is given in Table and of the additional less common clinical features (< 30%) in Table S2.…”
Section: Resultsmentioning
confidence: 99%
“…In 2015, May et al identified ZC4H2 variants in four additional families, including a large family with syndromic X‐linked ID (XLID; MRXS4), previously described as having Miles‐Carpenter syndrome (MCS; Miles & Carpenter, ) and characterized by XLID, exotropia, distal muscle wasting, microcephaly, congenital contractures, and low digital arches (May et al, ). Most recently, three simplex females with heterozygous de novo deleterious ZC4H2 were reported, including an early truncating nonsense variant and two microdeletions (Godfrey, Dowlatshahi, Martin, & Rothkopf, ; Okubo et al, ; Zanzottera et al, ). As a result of these findings, these various allelic syndromes are now referred to as ZC4H2‐associated rare disorders (ZARD).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, despite the fact that WWS is an X-linked recessive disorder, females carrying heterozygous ZC4H2 mutations may display a mild intellectual disability phenotype as well as subtle distal contractures and sometimes clubfoot ( 21 , 25 ). A recent study by Wang et al ( 22 ) demonstrated that mechanisms underlying X-chromosome inactivation (XCI) in females are not necessarily implicated in the disease phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…However, female patients show various symptoms especially in deletion and nonsense mutation cases, and some of them are considered to be associated with nonrandom X-chromosome inactivation (XCI) (Hirata et al, 2013). So far, 7 missense mutations, 1 nonsense mutation, 1 frameshift mutation, 1 chromosomal breakpoint in Xq11.2, and 4 deletions in ZC4H2 gene have been reported ( Figure 1) (Godfrey, Dowlatshahi, Martin, & Rothkopf, 2018;Hennekam, Barth, Van Lookeren Campagne, De Visser, & Dingemans, 1991;Hirata et al, 2013;Kondo et al, 2018;May et al, 2015;Okubo et al, 2018;Zanzottera et al, 2017). The clinical presentation and genetic changes in female patients have been summarized in Table 1.…”
mentioning
confidence: 99%